Difficulti message sign( an actor meaning) in monodramas show (Journal of the College of Basic Education, 2022)
The sign of monodrama passes through some difficulties because of the special of this theafre which the actor performs many characters and needs different of signs and meanings. The search rises a question:Does the actor in monodrama show build new informations which be able to open new ways and veriaty of meaning and message. The value of this research indicates the sign is rich in monodrama show and carries the responsibility of the show. The tarket of the search consertrates in discoving sign message and their working.The second indication two parts:First :sign message is in the text and show of monodrama.Second: sign working is in monodrama’s show.The researcher choses the samble in perpose in aplay (I search darkness) writing and directing by Awati of Naeem. The search appears some resalts…like.The actor Aziz Khioon didn’t creat abalance between his dialoge itself sammeried that dialogu to different signs which pushes the repeatiny and the fed up away and the main results that the production of signs needs an actor who knows different signs.